PATTERN OF USAGE OF SOCIAL NETWORKING SITES AND ITS INFLUENCE ON SELF-ESTEEM AND SOCIAL CAPITAL FORMATION AMONG EMERGING ADULTS: A CROSS SECTIONAL STUDY IN IDUKKI DISTRICT, KERALA. - ATHULYA THOMAS (SREE CHITRA TIRUNAL INSTITUTE FOR MEDICAL SCIENCES AND TECHNOLOGY, 2015)
Background: Social networking sites (SNS) enhance human relationships and decreases space in relationships by promoting computer mediated communication. Emerging adulthood (18-25 years) is the transitional period between adolescence and adulthood. Among them interactions in virtual world have definite roles in the physical, emotional, social and cognitive development. We studied usage of SNS and its influence on self-esteem and social capital formation among emerging adults. Method: Cross-sectional study was conducted among 455 emerging adults (43% male) in colleges of Idukki district. Cluster sampling was used and sample size was proportionate to strength. Study was done using self-reported questionnaire, had sections on assessing pattern of SNS usage, self-esteem (Rosenberg scale) and social capital (ISCC). Analysis was done in SPSS 21. Linear regression was done Results: Students were from different disciplines -Arts and Science (56%), Medicine (14%) and Engineering (30%). About 92% were dependent on their parents. Only 76% accessed SNS. Among them 57% accessed through smart phones. On an average they spend 60 minutes in SNS/day. Male students spent more time on SNS compared to female. Pattern of usage of SNS not associated with self-esteem. Communication activities, location and device used for access, age of respondents, friends in SNS and friends in real world are associated with social capital. Conclusion: About three-fourth of emerging adults access SNS. Among them half accessed through their smart phones. SNS is not associated with self- esteem among emerging adults, but it contributed positively on the formation of social capital among them.